Wednesday
March 22, 2017

Post a New Question

Posted by on Friday, March 28, 2014 at 5:00pm.

factor:

1) (x+y)^2 - (a+b)^2
= [(x+y) - (a+b)] [(x+y) + (a+b)]
= [x+y-a-b] [x+y+a+b]

2) 6x^4 - 6
= 6(x^4 - 1)
= 6(x^2-1)(x^2+1)

Is this right?

  • math help - , Friday, March 28, 2014 at 5:14pm

    1. x^2 +2xy +y^2 -a^2-2ab-B^2
    2. 6(x^4-1) = 6(x^2-1)(x^2 +1)

    = 6(x-1)(x+1)(x^2+1)

  • math help - , Friday, March 28, 2014 at 5:21pm

    #2 is ok, but not yet complete:

    x^2-1 = (x-1)(x+1)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question